Assessing parental awareness and concerns about children’s tobacco smoke exposure: a community-based analysis - Seydanur Yaylaoglu; Cihad Dundar (Archives of Public Health)
Abstract Background Information regarding children’s exposure to tobacco smoke, posing significant risks, is usually reliant on parental reports. We aimed to adopt the scale of parental perception of children’s tobacco smoke exposure (PPE) into Turkish, and investigate its correlation with sociodemographic factors. Methods The language and cultural adaptation of the original scale was carried out according to the international guidelines. The participants consisted of 250 females and 250 males living in Samsun province who are over the age of 18, have children younger than 18 years old, without any visual impairment or communication barrier. The survey forms were administered through face-to-face interviews between November 2022 and April 2023. Results Mean age of the parents was 36.7 ± 6.9 years. A total of 179 (35.5%) parents were current smokers, and 44% of the households had at least one parent who reported smoking indoors. The mean score of PPE scale was 4.9 ± 1.2. Female sex, parents with higher education, with healthcare profession and with no history of smoking had better awareness about children exposure to smoke. A positive correlation was found between educational level and PPE scale score (r = 0.13; p = 0.004). Parents not allowing smoking indoors or in the car, and those not bringing children to restaurants where smoking was allowed, had higher PPE scores. Conclusions There is a need for multidisciplinary and community-based interventions, with more effective enforcement and monitoring of smoking bans in enclosed spaces and children’s play areas.